The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1080/0886022x.2016.1208465
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of renal hemodynamics changes in Familial Mediterranean fever with color Doppler sonography

Abstract: RRI may be a marker that may be used in assessing resistance to renal blood flow, early renal damage, and progression of renal damage in FMF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
0
4
2
Order By: Relevance
“…Furthermore, renal artery RI values also in the microalbuminuric patient group were found higher than the normoalbuminuric patients. 11 Both renal parenchymal stiffness and both renal artery RI values in the microalbuminuric group were found higher than the normoalbuminuric group in FMF patients in our study. Right renal parenchymal stiffness was found higher in the group with homozygote M694V mutation than other mutation groups, and it was found higher in compound heterozygote mutation than the group with heterozygote and homozygote V726A mutation.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…Furthermore, renal artery RI values also in the microalbuminuric patient group were found higher than the normoalbuminuric patients. 11 Both renal parenchymal stiffness and both renal artery RI values in the microalbuminuric group were found higher than the normoalbuminuric group in FMF patients in our study. Right renal parenchymal stiffness was found higher in the group with homozygote M694V mutation than other mutation groups, and it was found higher in compound heterozygote mutation than the group with heterozygote and homozygote V726A mutation.…”
Section: Discussioncontrasting
confidence: 46%
“…In the study conducted by Sezer et al renal artery RI values were found higher in FMF patients than in the control group. Furthermore, renal artery RI values also in the microalbuminuric patient group were found higher than the normoalbuminuric patients 11 . Both renal parenchymal stiffness and both renal artery RI values in the microalbuminuric group were found higher than the normoalbuminuric group in FMF patients in our study.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…They found no significant difference in ADC values in other organs. A Doppler US study conducted by Sezer et al 27 on 79 FMF patients and 51 healthy individuals showed that renal artery resistive index values were significantly higher in FMF patients compared with healthy controls, and the renal artery resistive index values of the patients in the microalbuminuric subgroup were significantly higher in the patient group than in the nonalbuminuric subgroup. In addition, our study contributes to the literature by including the mean values of LSV and SSV in the healthy group and the relationship of these values with age and sex, as well as patients with FMF.…”
Section: Discussionmentioning
confidence: 97%
“…Clinical findings vary according to the organ where amyloidosis accumulates. If amyloid accumulates in the kidney, protein loss in the urine and renal failure usually develops (Scarpioni, 2016; Sezer et al., 2016). Pyrin protein also functions as the main regulatory component of the inflammasome complex and has been shown to play a role in many inflammasome‐induced autoinflammatory diseases (Kanneganti et al., 2018; Migita et al., 2018).…”
Section: Introductionmentioning
confidence: 99%